2016
DOI: 10.3346/jkms.2016.31.12.1943
|View full text |Cite
|
Sign up to set email alerts
|

Hemorheological Alteration in Patients Clinically Diagnosed with Chronic Liver Diseases

Abstract: Since liver function is changed by chronic liver diseases, chronic liver disease can lead to different hemorheological alterations during the course of the progression. This study aims to compare alterations in whole blood viscosity in patients with chronic liver disease, focusing on the gender effect. Chronic liver diseases were classified into three categories by patient’s history, serologic markers, and radiologic findings: nonalcoholic fatty liver disease (NAFLD) (n = 63), chronic viral hepatitis B and C (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The fluid viscosity in the poro-visco-elastic model is 3.1 mPas, which is below the commonly assumed whole blood viscosity of 3.5 mPas but above the viscosities given for microcirculation and interstitial fluid in the liver by [59]. In a recent study [75], observed an anti-correlation of blood viscosity with liver stiffness as measured by transient elastography. The authors suggested pathologic changes as the source of this anticorrelation.…”
Section: Porous Liver Modelingmentioning
confidence: 73%
See 1 more Smart Citation
“…The fluid viscosity in the poro-visco-elastic model is 3.1 mPas, which is below the commonly assumed whole blood viscosity of 3.5 mPas but above the viscosities given for microcirculation and interstitial fluid in the liver by [59]. In a recent study [75], observed an anti-correlation of blood viscosity with liver stiffness as measured by transient elastography. The authors suggested pathologic changes as the source of this anticorrelation.…”
Section: Porous Liver Modelingmentioning
confidence: 73%
“…Shear rate is a function of flow and vessel diameter, which vary widely throughout the liver [83]. We thus explicitly make the choice of reducing the model complexity by assuming an average Newtonian blood viscosity under systolic conditions as for example measured by [75]. The Biot parameters are interrelated, hence the sensitivity of the shear wave speed on one parameter depends on the choice of the others.…”
Section: Poro-visco-elastic Liver Modelmentioning
confidence: 99%
“…Furthermore, machine perfusion driven viability assessment during HMP/HOPE or NMP may support clinical decision in the acceptance or rejection of marginal liver allografts [ 4 , 6 , 184 ]. Besides refinement of the preservation techniques, the impact of hepatic dysfunction on macro- and micro-rheological parameters still need to be investigated, including metabolomics studies, to reveal better the local and systemic effects [ 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 ]. However, it would be interesting to overview it in a separate paper.…”
Section: Future Perspectives and Remaining Challengesmentioning
confidence: 99%
“…WBV was measured during surgery three times via a central venous catheter: at the beginning of surgery (i.e., skin incision) in the supine position without pneumoperitoneum, after 30 min in the STP with pneumoperitoneum, and at the end of surgery (i.e., peritoneal closure) in the supine position without pneumoperitoneum (Table 1). Blood samples (3 mL) were collected into evacuated test tubes (BD Vacutainer, K2 EDTA; Becton, Dickinson and Company, Franklin Lakes, NJ, USA) without venous stasis, and measured using an automated scanning capillary tube viscometer (Hemovister; Ubiosis, Seongnam, Republic of Korea): WBV at a high shear rate (300 s − 1 ) was recorded as systolic blood viscosity (SBV) and that at a low shear rate (5 s − 1 ) was recorded as diastolic blood viscosity (DBV) [22]. The reference intervals for WBV were 3.5-4.1 cP at 5 s − 1 and 9.4-13.0 cP at 300 s − 1 in male patients, based on the manufacturer's instructions.…”
Section: Measurement Of Wbvmentioning
confidence: 99%